The Influence of Supervisor Understanding on IRE Teacher Performance in State JHS in Bone Regency - Agus, Agus; Asnawi, Nur Rahmah; Adam, Adiyana; Swarga, Alim Bubu (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
The objective of this study is to examine the capacity of supervisors to comprehend the Islamic Religion Education (IRE) learning process at State Junior High School (State JHS) in Bone Regency, the performance of teaching staff, and the impact of these two factors on one another. The research design is correlational, and the analysis techniques employed are descriptive and inferential statistics, including percentage formulation, product-moment correlation coefficient, regression, and coefficient of determination. The sample for this study comprised 77 teachers, selected from a population of 154. The findings indicated that the supervisor demonstrated a commendable aptitude for comprehending the IRE learning process at State JHS in Bone Regency, with a score of 68%. Similarly, teacher performance in the IRE learning process was also classified as good, with a score of 84%. Furthermore, the supervisor’s capacity to understand the learning process was observed to exert a direct influence on teacher performance in the learning process, with a percentage of 37%.